2018
DOI: 10.1007/s00592-018-1225-9
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine restores autophagy and cardiac dysfunction in rats with streptozotocin-induced diabetes mellitus

Abstract: DEX reduces cardiac dysfunction and impaired autophagy in DM rats. This study reinforces our understanding of the potential anti-autophagic effect of DEX in patients with diabetic cardiomyopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…LPS pretreatment could obviously suppress autophagy and induce intracellular injury. However, DEX significantly restored autophagy in our study, consistent with the results of Oh et al (2019). According to these results, we confirmed that DEX can restore the lack of autophagy induced by LPS.…”
Section: Discussionsupporting
confidence: 91%
“…LPS pretreatment could obviously suppress autophagy and induce intracellular injury. However, DEX significantly restored autophagy in our study, consistent with the results of Oh et al (2019). According to these results, we confirmed that DEX can restore the lack of autophagy induced by LPS.…”
Section: Discussionsupporting
confidence: 91%
“…However, the effects of DEX on ERS and the resulting apoptosis have not yet been thoroughly elucidated. In previous studies, DEX exhibited a protective role in the hearts of diabetic mice by interfering with ERS or autophagy, thereby suppressing IRI (6,23); however, the results were partially attributed to the diabetes context. Furthermore, researchers have focused on the study of cells other than cardiomyocytes, such as endothelial cells, under IRI or hypoxia/reoxygenation (H/R) conditions (24,25), and have examined several crucial ERS chaperones, proteins and apoptosis indicators that are produced by organs other than the heart under IRI or H/R conditions (6,(26)(27)(28)(29)(30).…”
Section: Dexmedetomidine At a Dose Of 1 µM Attenuates H9c2 Cardiomyocmentioning
confidence: 84%
“…However, it is difficult to simulate this type of injection in rats. Several studies have reported the beneficial effects of Dex on various diseases with mechanisms of action attributed to anti-autophagy and inflammation regulation (Oh et al, 2019 ; Sun et al, 2019 ). Consistent with these previous studies, our experimental results showed that Dex decreased the expression of GSDMD and GSDMD-N and ameliorated brain edema, neurobehavioral deficits, and neuronal injury in a rat model of SAH.…”
Section: Discussionmentioning
confidence: 99%